Network pharmacology to investigate the pharmacological mechanisms of muscone in Xingnaojing injections for the treatment of severe traumatic brain injury - Liu,Zhuohang; Li,Hang; Ma,Wenchao; Pan,Shuyi (PeerJ, 2021)
Background Xingnaojing injections (XNJI) are widely used in Chinese medicine to mitigate brain injuries. An increasing number of studies have shown that XNJI may improve neurological function. However, XNJI’s active ingredients and molecular mechanisms when treating traumatic brain injury (TBI) are unknown. Methods XNJI’s chemical composition was acquisited from literature and the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. We used the “absorption, distribution, metabolism, and excretion” (ADME) parameter-based virtual algorithm to further identify the bioactive components. We then screened data and obtained target information regarding TBI and treatment compounds from public databases. Using a Venn diagram, we intersected the information to determine the hub targets. Cytoscape was used to construct and visualize the network. In accordance with the hub proteins, we then created a protein–protein interaction (PPI) network using STRING 11.0. Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were analyzed according to the DAVID bioinformatics resource database (ver. 6.8). We validated the predicted compound’s efficacy using the experimental rat chronic constriction injury (CCI) model. The neuronal apoptosis was located using the TUNEL assay and the related pathways’ hub proteins were determined by PCR, Western blot, and immunohistochemical staining. Results We identified 173 targets and 35 potential compounds belonging to XNJI. STRING analysis was used to illustrate the protein–protein interactions and show that muscone played a fundamental role in XNJI’s efficacy. Enrichment analysis revealed critical signaling pathways in these components’ potential protein targets, including PI3K/AKT1, NF-kB, and p53. Moreover, the hub proteins CASP3, BCL2L1, and CASP8 were also involved in apoptosis and were associated with PI3K/AKT, NF-kB, and p53 signaling pathways. We showed that muscone and XNJI were similarly effective 168 h after CCI, demonstrating that the muscone in XNJI significantly attenuated neuronal apoptosis through the PI3K/Akt1/NF-kB/P53 pathway. Conclusion We verified the neuroprotective mechanism in muscone for the first time in TBI. Network pharmacology offers a new approach for identifying the potential active ingredients in XNJI.
Keywords: XNJI; Muscone; Protein targets; Network analysis; Traumatic brain injury